AN ASSOCIATION OF THE CLINICAL MANIFESTATIONS OF NSAID GASTROPATHY WITH UPPER GASTROINTESTINAL MOTOR DISORDERS IN PATIENTS WITH RHEUMATOID ARTHRITIS - D Abdulganiyeva; N E Belyanskaya; E L Nasonov (Научно-практическая ревматология)
Objective: to evaluate upper gastrointestinal (GI) motor disorders in diclofenac sodium-treated patients with rheumatoid arthritis (RA), by using 24-hour pH-metry, and their association with the clinical manifestations of gastropathy induced by nonsteroidal anti-inflammatory drugs (NSAIDs) (NSAID gastropathy). Subjects and methods. A study group included 39 patients diagnosed as having RA, 14 subjects formed a control group. All the included subjects underwent a clinical examination, endoscopic studies of the esophagus, stomach, and duodenum, and 24-hour gastric and esophageal pH monitoring (Gastroscan-24, Istok-Sistema Research-and-Production Association, Fryazino, Moscow Region). Results and discussion. Comparing the results of 24-hour intraesophageal and intragastric pH studies in RA patients and healthy individuals revealed differences in nocturnal acidity values. The RA group showed lower nocturnal pH values than the controls (p < 0.05). The obtained pH values may indirectly suggest that the RA patients have duodenogastroesophageal reflux. Analysis of 24-hour pH metric readings indicated the concurrence of gastroesophageal and duodenogastric refluxes in 37%. It is in this group that displayed a clinical decussation of pain and dyspeptic syndromes (p < 0.05). Conclusion. The upper GI motor disorders found in the RA patients taking NSAIDs may play an important role in the development of clinical manifestations of NSAID gastropathy and, probably, a certain group of patients must undergo medical correction of the symptoms related to dysmotility.